Solving Two Species Lotka-Volterra Biological Model Using Sawi Transformation - Jamaludin, Nur Zawani; Abd Latif, Noor Azliza; Che Him, Norziha (Enhanced Knowledge in Sciences and Technology, 2026)
The paper explores the use of Sawi Transformation to solve the two species Lotka-Volterra predator-prey model, which is ruled by an ordinary differential equation (ODE) system that is nonlinear. The main aim is to show how this fundamental transformation is working to simplify nonlinear systems through the reduction of the complexity of the system by transforming it into algebraic equations to enable semi-analytical solutions with less computation effort. Maple 2015 is used to obtain iterative solutions to both the classical and modified Lotka-Volterra models. The findings are then compared the Variational Iteration Method (VIM). The comparison proves that the Sawi Transformation method has highly accurate results which are equally efficient. These results confirm that Sawi Transformation is a robust valid instrument in solving nonlinear dynamical systems with a lot of success in ecological and biological modelling.